Penerapan Teknik Token Economy dalam Meningkatkan Kedisiplinan Anak Usia 5 - 6 Tahun di Kelompok Bermain Taman Ceria Bandung - Maryono, Awanis Ghassani; Erhamwilda; Dewi Mulyani (UNISBA Press, 2023)
Abstract. This research is motivated by the discipline of children aged 5-6 years in the Taman Ceria Bandung Playgroup which is not optimal. The purpose of this research is to improve children's discipline through the application of token economy techniques. The research method used is collaborative action research or collaborative classroom action research. The research subjects were children aged 5-6 years, totaling 8 people consisting of 4 boys and 4 girls. Data collection techniques using observation and documentation. The data analysis technique performed was a qualitative descriptive analysis. Success indicators set at least 75% average score per child. The research was carried out in two cycles. The results of this study indicate that there is an increase in discipline after implementing the token economy technique. Referring to the percentage of Arikunto's assessment indicators in the pre-cycle observations, it showed that 5 out of 8 children had an average score that entered the growing category. In Cycle 1 it showed that 8 children had an average score that entered the developing category as expected. In cycle 2 it shows that 7 children with an average score enter the very well developed category and 1 child with an average score enter the developing category according to expectations. This shows an increase in discipline using the token economy technique. Abstrak. Penelitian ini dilatarbelakangi oleh kedisiplinan anak usia 5-6 tahun di Kelompok Bermain Taman Ceria Bandung yang belum optimal. Tujuan dari penelitian ini adalah untuk meningkatkan kedisiplinan anak melalui penerapan teknik token economy. Metode penelitian yang digunakan adalah collaborative action research atau penelitian tindakan kelas kolaboratif. Subjek penelitian adalah anak umur 5-6 tahun yang berjumlah 8 orang terdiri dari 4 orang laki-laki dan 4 orang perempuan. Teknik pengumpulan data menggunakan observasi dan dokumentasi. Teknik analisis data dilakukan adalah analisis deskriptip kualitatif. Indikator keberhasilan yang ditetapkan minimal 75% rata-rata skor per anak. Penelitian dilaksanakan dalam dua Siklus. Hasil penelitian ini menunjukan bahwa adanya peningkatan kedisiplinan setelah diterapkan teknik token economy. Merujuk pada presentase indicator penilaian Arikunto pada observasi Pra Siklus menunjukan 5 dari 8 anak memiliki rata-rata skor yang memasuki kategori mulai berkembang. Pada Siklus 1 menunjukan 8 anak memiliki rata-rata skor yang memasuki kategori berkembang sesuai harapan. Pada siklus 2 menunjukan bahwa 7 anak rata-rata skor memasuki kategori berkembang sangat baik dan 1 anak rata-rata skor memasuki kategori berkembang sesuai harapan. Hal ini menunjukan adanya peningkatan kedisiplinan menggunakan teknik token economy.